Enhancing the CRI and lumen output for the 6600 K WLED with convex-dual-layer remote phosphor geometry by applying red-emitting MGSR3SI2O8:EU2+,MN2+ phosphor - Thuc Minh Bui; Nguyen Thi Phuong Loan; Phan Xuan Le; Nguyen Doan Quoc Anh; Anh Tuan Le; Le Van Tho (Institute of Advanced Engineering and Science, 2020)
The traditional white LED product established with a single chip and a single phosphor results in a low color rendering index (CRI). The upgrade of LED package is comprised of two chips and one phosphor material and gives the higher CRI while keeping high luminous efficiency. Based on previous findings, the research paper performs the application of the two chips and two phosphors to enhance the color tunability of LEDs with different amounts and intensities of the two employed phosphors. Additionally, a color design model is built to serve the purpose of bettering the color fine-tuning of the white-light LED module. The maximum value of the difference between the measured CIE 1931 color coordinates and that of the simulated model is approximately 0.0063 around the 6600 K correlated color temperature (CCT). From the results, this study offers a quick approach to achieve the color fine tuning of a white-light LED module with a high CRI and luminous efficiency.